Removal of Diclofenac Pharmaceutical Residues from Wastewater - Aly, Fatma (AUC Knowledge Fountain, 2023)
As diseases worldwide and in Egypt are increasing by time, developing, and producing new medicines is massively expanding. The use of pharmaceutical compounds is rising worldwide. Diclofenac compound is used in plenty of different kinds of drugs as a nonsteroidal anti-inflammatory drug “NSAID” treating inflammation, osteoarthritis and rheumatoid. Due to excessive exposure to diclofenac -from humans and animals, large amounts are found in the water streams and the environment. Most of the conventional treatment methods is not capable of the complete removal of the diclofenac. Therefore, most of it is thrown back into the water bodies badly affecting the environment, forming a closed loop of diclofenac consumption unintentionally. The more diclofenac used, the more it can cause serious endangerments to the environment, not only aquatic life but also human beings. Therefore, the diclofenac was put on the EU Water Framework Directive watch list. Adsorption studies conducted in batch mode and continuous flow mode reactors demonstrated the ability of removal diclofenac compound from wastewater using activated carbon material. For the purpose of determining adsorption isotherms, a batch adsorption experiment has been carried out, while column design experiments were assessed through a lab scale column design including three variables: initial diclofenac concentration (3 – 20 mg/l), bed height (3.3 – 7.5 cm) and feed flow rate (3 – 6 ml/min). The research conducted that Langmuir isotherm was a better isotherm fit than Freundlich. It also proved that the higher the bed height in column experiments the higher the percentage removal of diclofenac, reaching 93% at bed height 7.5 cm. Therefore, the optimum and sustainable method to remove the diclofenac compound from its primary source -at wastewater treatment plants- is studied using activated carbon in two different operating modes to protect the environment before the contamination reaches any natural stream and causes further damage.